Evaluation of avian papillomavirus occurrences and effective sampling materials for screening purpose in bird species through systematic review and meta-analysis - Najihah, Nurulhuda; Nurul Najian, Aminuddin Baki; Syahir, Amir; Abu, Jalila; Ho, Kok Lian; Siang Tan, Wen; Mariatulqabtiah, Abdul Razak (Universiti Putra Malaysia, 2023)
Papillomaviruses (PVs), double-stranded circular DNA viruses, typically cause regressing papillomas (warts) on mucosal or keratinized epithelia of a wide spectrum of species. The viruses largely infect mammals, whereby PV infections in humans, bovines, and rabbits are extensively reported. However, studies on non-mammalian PVs, particularly avian ones, are relatively lacking and worthy of investigation. This study performed a meta-analysis post-systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement guidelines to evaluate the occurrences of avian papillomaviruses (APVs) in bird species and effective materials used for virus detection. The electronic databases Science Direct, Medline via PubMed, and Google Scholar were used to search for the journal articles. Upon article eligibility check, the QUADAS-2 was employed to assess the data. Of 1139 records, 31 were eligible for full-text review, but only 9 were significant for the final review. The results showed that APVs are highly prevalent among the Fringillidae family, with a proportion of 81%, followed by Laridae (30%) and Anatidae (13%). The pooled prevalence of APV in tissue samples was 38%, while in swab samples was 13%. Only one study reported positive APV from fecal materials (0.4%); hence, the reliability comparison between these three samples was not performed. This study concluded that APVs are most prevalent in the Fringillidae bird family, while tissues are the most suitable biological samples for APV screening and should be considered as a single sample material. From epidemiology, knowledge of APV incidences and distribution may assist in controlling papillomatosis in bird species.